Toward Cost-Effective Reservoir Simulation Solvers on GPUs (Advances in Applied Mathematics and Mechanics, 2021)
In this paper, we focus on graphical processing unit (GPU) and discuss howits architecture affects the choice of algorithm and implementation of fully-implicitpetroleum reservoir simulation. In order to obtain satisfactory performance on newmany-core architectures such as GPUs, the simulator developers must know a greatdeal on the specific hardware and spend a lot of time on fine tuning the code. Portinga large petroleum reservoir simulator to emerging hardware architectures is expensiveand risky. We analyze major components of an in-house reservoir simulator and investigatehow to port them to GPUs in a cost-effective way. Preliminary numericalexperiments show that our GPU-based simulator is robust and effective. More importantly,these numerical results clearly identify the main bottlenecks to obtain idealspeedup on GPUs and possibly other many-core architectures.